Utmana eller utmanas : Om läsvanor och läslust hos elever på Kulturgymnasiet - Isaksson, Elin; Åström, Helena (2015)
The purpose of this study is to examine joy of reading among students who attend the Cultural Program at the upper secondary school in Luleå. The study presents the students’ experiences of reading fiction, at school as well as on their leisure time. The study also examines the students’ thoughts about preparatory- and post-production work in their literature education. In connection to this, we have examined how the teachers perceive the students’ reading habits and how they work to stimulate the students’ joy of reading. We also compare the study with previous studies regarding the subject ‘joy of reading’ to see whether our results deviate from similar studies within the field. The study is based on interviews with teachers and students, as well as an online questionnaire which was filled out by 31 students. The two teachers who were interviewed taught grade 1, 2 and 3 and the questionnaire was answered by the students from these grades. Two students, a boy and a girl, participated in the student interview. The results show that the students read more in school than on their leisure time. Knowledge of the students’ reading abilities and interests are important aspects in finding suitable literature for each individual student. During their interviews, the teachers expressed the importance of prior knowledge of the students’ reading- and writing abilities as well as the students’ experiences and perception of fiction in general. In order to support and stimulate students’ joy of reading, the teachers express that each teacher needs to assess on which level the students are regarding their reading comprehension. The students expressed that they appreciate fiction to which they can relate. One of the teachers discussed how she tries to choose fiction with regards to age, students’ interests and to current themes. However, the students expressed that they do not feel included when it comes to choosing which literary text they are supposed to read in school and that their interests and hobbies are not taken into ...